2014
DOI: 10.1093/tropej/fmu056
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Symptomatic Multiple Cardiac Rhabdomyomas Associated with Tuberous Sclerosis Complex in a Newborn Receiving Everolimus

Abstract: As we observed in our patient, in cases with inoperable symptomatic rhabdomyomas associated with TSC, everolimus, an mTOR inhibitor, may be the treatment of choice, which should be confirmed with additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…These authors reported on a case of a 7‐year‐old patient with TSC who had everolimus for treatment of SEGAs and experienced unexpectedly regression of a large left ventricular cardiac rhabdomyoma. This finding has been successfully reproduced in several case reports of RHMs …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These authors reported on a case of a 7‐year‐old patient with TSC who had everolimus for treatment of SEGAs and experienced unexpectedly regression of a large left ventricular cardiac rhabdomyoma. This finding has been successfully reproduced in several case reports of RHMs …”
Section: Discussionsupporting
confidence: 68%
“…Although cardiac RHMs are known as the most common primary cardiac tumors that are histologically benign, their behavior may be relevant to cardiac function due to their size or location. In up to 86% RHMs are associated with TSC . Mammalian target of rapamycin (mTOR) inhibitors that downregulate the overactive mTOR pathway in TSC have been shown to be a specific treatment option in TSC‐related manifestations as SEGA or AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are not approved by Food and Drug Administration, mammalian target of rapamycin (mTOR) inhibitors are currently under investigation as a treatment option for CRHMs especially for those with technical difficulties for surgery (11). Everolimus appears to be a reasonable therapeutic alternative to surgery in symptomatic infants in whom spontaneous regression cannot be awaited (5) and succesful results are reported with everolimus (3,5,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Everolimus appears to be a reasonable therapeutic alternative to surgery in symptomatic infants in whom spontaneous regression cannot be awaited (5) and succesful results are reported with everolimus (3,5,11,12). Adverse effects of everolimus include myelosuppression, peripheral edema, increased creatinine level, diarrhea, nausea, urinary tract infections, hyperlipidemia, hypertriglyceridemia, mouth ulcers, hepatotoxicity, proteinuria, and impaired wound healing (13).…”
Section: Discussionmentioning
confidence: 99%